Effects of nano-carbon reinforcement on the swelling and shrinkage behaviour of soil - Mohd Raihan Taha; Alsharef, Jamal M.A.; Al-Mansob, Ramez A.; Ahmed Khan, Tanveer (Penerbit Universiti Kebangsaan Malaysia, 2018)
In this study, the performance of two types of nanocarbons (NCs), namely carbon nanotubes (CNTs) and carbon nanofibers (CNFs), on the three-dimensional shrinkage and swelling properties of three clayey soils were investigated. The specimens of soil mixed with clay with bentonite contents of 0, 10 and 20% by weight of dry soil. NC contents of 0.05, 0.075, 0.10 and 0.20% were chosen to investigate the influence of different NC types, CNTs and CNFs. All soil specimens were compacted under maximum dry unit weight and optimum water content conditions by using standard compaction tests. The physical and mechanical characteristics of the reinforced samples were then determined. These included the desiccation cracking area, used to determine the crack intensity factor (CIF), as well as the shrinkage and swelling. The CIF for the soil specimens without NCs were higher than the soil specimens with NC additives. These results show that NCs decrease the development of desiccation cracks on the surface of compacted samples. The shrinkage and swelling tests showed that the rate of volume changing of the compacted soil specimens reduced with the increasing of NCs.